EFFECT OF ORGANIC MATERIAL COMPOSTED BY Trichoderma Spp. TO CHILI PEPPER IN CONTAMINATED MEDIA BY Fusarium oxysporum - Setiawan, Aris; Rianto, Fadjar; Palupi, Tantri (Fakultas Pertanian Universitas Tanjungpura, 2018)
ABSTRACT Chili pepper is one of horticultural crop that is quite important in Indonesia, it has a high economic value. Chili pepper plant productivity tends to fluctuate due to Fusarium wilt disease. This study aims to suppress the development of F. oxysporum disease in chili pepper plant using compost inoculated by Trichoderma spp. which de Decomposers and as biological agent. This research was conducted at Plant Disease Laboratory Faculty of Agriculture, University of Tanjungpura Pontianak. The experiment ased a randomized block design with 4 treatments: (Trichoderma spp. that has inoculated capability as dissolving cellulosa), (Trichoderma spp. Isolates as antagonists, and mixed two isolates Trichoderma spp. cellulose solvent with antagonist), and Control (EM4 as decomposer). This research is divided into two stages, on nursery and planting in the field. Trichoderma both as decomposer and antagonist treatment can suppress disease incidence at nursery 14.21%. composting give Trichoderma spp. has ent been able to stop the development Fusarium attacks on chili papper although the plant can still produce the fruit.